Arts education offered by Greek Universities to future pre-school and primary school teachers - Sotiropoulou - Zormpala, Marina; Trouli, Kalliopi; Linardakis, Michail (Preschool and Primary Education, 2014)
The arts education of generalist teachers in pre-school and primary schools seems to be a matter of great importance, because it is they who mainly practice arts education in school with children up to the age of 12. The purpose of this study is to describe and evaluate the arts education offered to pre-service pre-school and primary school teachers in the departments of education of all universities in Greece. The data were collected from two sources. First, data on the characteristics of the arts courses examined were collected from university documents on the syllabus of every department in the study. Second, a questionnaire was used to collect data on what the students at the examined departments believed about the arts education they were getting. The study showed that the arts education offered in Greek departments of education has developed in a peculiar manner and has problematic aspects. Even today, it is lacking in quantity, of a lower standard than other courses, and with an orientation that either is more mechanical or more theoretical than it should be. Both the analysis of the documents and of the students’ views highlight changes that seem to be necessary to qualitatively and quantitatively improve the arts education and training provided in the departments examined.